TRANSFORMATION OF QUALITY MANAGEMENT TOWARDS EFFECTIVE PARTNERSHIP PROGRAM DESIGN IN THE ERA OF COMMUNITY DIGITALIZATION - Ani, Emi Dwi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze the implementation of Management Control Circle (QCC) through partnerships at RA Raudlatul Hasan Condong Gading Probolinggo, as an effort to strengthen institutional quality control. Quality Control Circle management is an important strategy in improving quality control in educational institutions, which can have a positive impact on the sustainability and quality of the institution itself. Strengthening QCC management has become increasingly vital in the digital era, which spurs institutions to adapt and innovate to maintain relevance and service quality. This research uses a qualitative approach with data collection techniques in the form of interviews, observation and documentation. The collected data was analyzed using data reduction and presented in the form of a data display which ended with drawing conclusions. The research results show that QCC management at RA Raudlatul Hasan Condong Gading is implemented through four main stages: planning, partnership program, school branding, and evaluation. Effective implementation of QCC contributes to improving the quality of the institution, which is reflected in the increasing recognition of RA Raudlatul Hasan in the community and the increase in the number of students from year to year. These findings show that partnerships and branding strategies integrated with QCC management can strengthen the institution's position in facing the challenges of the digital era while increasing competitiveness and the quality of education provided